Asset Allocation Policy Analysis, Share Selection, and Level of Mutual Fund Risk in Indonesia - Rizka Irawati; febrianti salsabilah; Alifah Assa Diyah (Universitas Mercu Buana, 2022)
This research aims to analyze the performance of equity mutual funds in Indonesia by observing their asset allocation policy, stock selection, and risk level. This research uses pooled data, the data choosing with purposive sampling. Data availability at: www.portalreksadana.com, www.bi.go.id,www.lps.go.id, and www.finance.yahoo.com. The sample consists of 63 items of equity mutual funds since January 2017 until December 2019. The hypothesis of this research are examined using the multiple regression. The result of this research shows that equity mutual funds performance is affected by asset allocation policy, stock selection, and risk level. It indicates that mutual funds performance is determined by those activities of investment managers and market return conditions